Gamified web-based learning to improve evaluation skills in teacher professional education courses - Hidayat, Wahyu Nur; Widiyanti, Widiyanti; Ichwanto, Muhammad Aris; Prasetya, Didik Dwi; Akbar, Asna Isyarotul; Prihandicha, Adiftya Bayu; Cakir, Gulsun Kurubacak (Jurnal Inovasi Teknologi Pendidikan, 2025)
Education is a key pillar in the development of individuals and society. In this digital era, technology has revolutionized learning by expanding access and improving the quality of the learning process. One of the recent innovations is the use of web-based learning (WBL), which, although flexible, often lacks interaction elements, thus reducing user engagement. To address this, this research proposes a platform, “Meja Guru Academy,” that integrates gamification elements in WBL to improve the learning evaluation skills of Teacher Professional Education (PPG) students. This research utilizes the Design Thinking approach, which involves the stages of empathy, problem definition, idea development, prototyping, and evaluation—the data collection method through questionnaires produced quantitative and qualitative data for system validation. Content experts rated the platform's educational material at 85.33%, indicating exceptional alignment with learning objectives, while media experts provided a score of 89.60%, highlighting effective usability. User testing with PPG students yielded a strong System Usability Scale (SUS) score of 79, suggesting the platform is highly user-friendly. Additionally, the User Experience Questionnaire (UEQ) results indicated positive user perceptions across multiple aspects, with high ratings in pragmatic quality attributes such as perspicuity and efficiency, and hedonic qualities including stimulation and novelty. Overall, Meja Guru Academy presents an innovative and effective solution for advancing PPG students' evaluation competencies, fostering engagement and self-directed learning through gamified WBL.